Use of EDTA on Bond of Adhesives to Fluorotic Enamel. (2022) - Muniz, LP; Moreira, PHA; Ferreira, MWC; Reis, A; Cardenas, AFM; Loguercio, AD; Siqueira, FSF
Abstract : Purpose/Aim: To compare the effect of active pre-conditioning with 17% ethylenediaminetetraacetic acid (EDTA) vs. 37% phosphoric acid (PA) on the resin-enamel microshear bond strength (μSBS), enamel-etching pattern, and in-situ degree of conversion (in-situ DC) of four universal adhesive systems on sound enamel and fluorotic enamel. Materials and Methods: 224 extracted human molars (112 with no fluorosis and 112 with fluorosis) were sectioned into 4 parts and divided into 16 experimental groups based on the enamel surface (sound or fluorotic enamel), adhesive system (Clearfil Universal Bond [CUB], Futurabond U [FBU], iBond Universal [IBU], or Scotchbond Universal [SBU]), and enamel conditioning agent (phosphoric acid [PA] mode or EDTA mode). The specimens were stored for 24 h and tested under shear stress at 1.0 mm/min (μSBS). The adhesive-enamel interfaces were evaluated for in situ DC using micro-Raman spectroscopy. The enamel-etching pattern was evaluated using a scanning electron microscope. The SBS and in situ DC data were analyzed separately using three-way analysis of variance and Tukeys post-hoc test (α = 0.05). Results: Sound enamel showed higher μSBS and DC values as compared to fluorotic enamel (p < 0.05). However, no significant difference was observed for μSBS, DC (p > 0.05), and etching patterns when the PA and EDTA modes were compared in sound and fluorotic enamel. Moreover, CUB and SBU showed higher mean values of μSBS than that of FBU and IBU in both sound and fluorotic enamel (p < 0.05). Conclusions: As compared to PA, active pre-conditioning with EDTA showed similar μSBS values and enamel etching patterns for all the adhesive systems in fluorotic enamel, without compromising the in situ DC.